The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/lary.29485
|View full text |Cite
|
Sign up to set email alerts
|

Frailty as a Predictor of Postoperative Complications Following Skull Base Surgery

Abstract: Objective/Hypothesis Frailty has emerged as a powerful risk stratification tool across surgical specialties; however, an analysis of the impact of frailty on outcomes following skull base surgery has not been published. The aim of this study was to assess the validity of the 5‐factor modified frailty index (mFI‐5) as a predictor of perioperative morbidity and mortality in patients undergoing skull base surgery. Methods A mFI‐5 score was calculated for patients undergoing skull base surgeries using the National… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 30 publications
1
30
0
Order By: Relevance
“…We used the mFI-5 as a measure of frailty. Previously, mFI-5 has been documented as an effective predictor of postoperative morbidity and mortality in neurosurgical patients including those undergoing spine surgery [ 20 , 28 - 30 ]. The mFI-5 categorical assessment was reported to be essentially equivalent to the 11-factor modified frailty index (mFI-11) score for spine surgery patients [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We used the mFI-5 as a measure of frailty. Previously, mFI-5 has been documented as an effective predictor of postoperative morbidity and mortality in neurosurgical patients including those undergoing spine surgery [ 20 , 28 - 30 ]. The mFI-5 categorical assessment was reported to be essentially equivalent to the 11-factor modified frailty index (mFI-11) score for spine surgery patients [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…Previously, mFI-5 has been documented as an effective predictor of postoperative morbidity and mortality in neurosurgical patients including those undergoing spine surgery. [20,[28][29][30] The mFI-5 categorical assessment was reported to be essentially equivalent to the 11-factor modified frailty index (mFI-11) score for spine surgery patients. [20] The mFI-5 score was calculated for each patient based on the presence of DM, hypertension, CHF, COPD, and dependent functional status (Table 2).…”
Section: Modified Frailty Index-5 (Mfi-5)mentioning
confidence: 99%
“…[3][4][5] Recent studies have demonstrated the clinical value of frailty-diminishing physiological reserve associated with comorbidity burden-as a predictor of morbidity and mortality across various skull base procedures. [6][7][8] However, this frailty-outcome relationship is poorly characterized for patients undergoing cerebrovascular surgery. This gap in understanding is critical because patients with neurovascular pathologies often have significant comorbidity profiles leading to postoperative complications like intracranial hemorrhage and reoperation.…”
Section: Tang Et Almentioning
confidence: 99%
“…We would like to thank Dr. Niño and colleagues for their letter highlighting considerations about the role of frailty in assessing perioperative risk in patients undergoing skull base surgery. 1 The authors identify other important factors that influence morbidity and mortality, including tumor biology, proximity to critical structures, and surgical approach among many others. We underscore that the modified 5-item frailty index (mFI-5) was not designed nor claimed to be an allencompassing risk stratifier.…”
mentioning
confidence: 99%